The spirit of the law versus the letter of the law: the nature of correlation - V. V. Sorokin (Правоприменение, 2021)
The subject of the research is the categories “the spirit of the law” and “the letter of the law” in their regulatory sense.The purpose of the research is to confirm or disprove hypothesis that the concept of “the spirit of the law” fundamentally impacts the methodology of legal research, legal con-sciousness and the mechanism of legal regulation.The methodology for researching the spirit of the law presupposes an adequate selection of means of knowledge. It is impossible to study the spirit of the law with the tools of ma-terialism or economic determinism. The spiritual-moral, axiological, metaphysical, systemic methods and the method of synthesis are preferred for the study of the spirit of the law. The legal system of society ceases to meet the elementary requirements of the formation of a person's legal consciousness, his improvement and spiritual health when the spirit of the law is denied. It is generally impossible to understand how law functions and achieves a regulatory effect using the dogmatic, positivist approach to law as a dominant method of cognition.The main results, scope of application. The problem of the operation of the spirit of the law is one of the ignored problems of legal practice. If the legal act is at odds with the spirit of the law, the law enforcer faces a difficult choice: either morality or law. This dilemma is fraught with serious conflicts both in the mental, psychological sphere of the law enforce-ment officer himself, and between all participants in the legal process. Every person has an internal imbalance if he makes decisions and performs actions that are contrary to his con-science. Jurisprudence, which adequately perceives the subordination between the spirit of the law and the letter of the law, warns against the temptation to consider law as a sphere independent of spiritual absolutes. The current law is not exactly what is set out in the texts of regulatory acts. Distinguishing between the spirit of the law and the letter of the law, therefore, requires special types of interpretation of texts (broad, restrictive), as well as analogies of legislation and analogies of law.